Validitas dan Reliabilitas Kuesioner Kidney Knowledge Survey (KiKS) Bahasa Indonesia pada Pasien Penyakit Ginjal Kronik - Tigo Ramansyah Prawira Negara; Hadi Sunaryo; Siti Fauziyah (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Background: Indonesia's chronic kidney disease population reached 638.178 people in 2023. Assessing patients’ knowledge regarding chronic kidney disease is essential to evaluate their understanding, which will affect self-management behavior and patient therapy outcomes.  Objective: This study aims to prove the validity of the Kidney Knowledge Survey Questionnaire (KiKS) as a theory-based self-management intervention instrument for the Indonesian population. Method: This study began with permission from the questionnaire authorization holder, forward translation, back translation, expert team assessment (content validity), verification, and reconciliation by the authority holder. It was then continued with construct validity and reliability tests on outpatients with chronic kidney disease. Results: The forward translation stage involved an independent language institution (previously unfamiliar with the KiKS questionnaire) and back translation by a translator whose mother tongue is English. Assessment of the back translation showed that the adaptation into Indonesian was valid. The content validity test gave an I-CVI value of 1 and a CVR of 1, except for question no. 9 was declared invalid (I-CVI value = 0.5 and CVR = 0). Construct validation and reliability tests on 30 chronic kidney disease patients showed that each question in the Indonesian version of the KiKS was valid with r> 0.306 and Cronbach's alpha of 0.819.  Conclusion: The Indonesian language version of the KiKS questionnaire instrument is valid and reliable in determining the level of knowledge of chronic kidney disease in chronic kidney disease patients.